A cysteine enzyme hemostat for efficient heparin-tolerant blood coagulation. Issue 5 (10th January 2023) - Lin, Mengchi; Yu, Lisha; Xiao, Liping; Fan, Jie
Abstract : A papain-based hemostat is prepared to convert fibrinogen into fibrin and promote hemostasis in a heparinized system where thrombin loses its function, and the excellent hemostatic performance is confirmed in the heparinized system. Abstract : It is challenging to stop bleeding effectively in patients treated with heparin which leads to enhanced risk of uncontrolled bleeding during operation. Herein, we report an easy-to-use and heparin-tolerant hemostatic agent based on a thrombin-like cysteine enzyme (papain), which catalyzes the hydrolysis of fibrinogen and cross-linking of fibrin clots. A papain-based hemostat with increased procoagulant activity is developed through immobilizing papain on the cellulose carrier, which displays short clotting time in both normal and heparinized plasmas. The excellent hemostatic performance of the papain-based hemostat is further confirmed with reduced hemostatic time and limited blood loss in a mouse tail amputation model, rabbit auricular artery injury model and rat liver injury model, in which a natural coagulation system fails to function on account of heparin. This bio-hemostat has great potential to reverse the effect of heparin and stop topical hemorrhage rapidly in surgical procedures.